Focused Ultrasound Ablation of an Arteriovenous Malformation Model - Jones, Jesse; Bolding, Mark; Ullman, Henrik; Kaneko, Naoki; Tateshima, Satoshi (Frontiers in Neurology, 2021)
Brain AVMs are rare but serious vascular lesions that often pose a management dilemma between the risk of various treatment modalities and uncertain natural history during observation. We describe preliminary data on the use of focused ultrasound as a novel therapeutic strategy. In an AVM model, one session of ultrasound gradually reduced flow through the lesion without inducing rupture. Due to its non-invasive yet immediate ablative effects, focused ultrasound may allow safer treatment of AVMs. However, further studies are needed to clarify its efficacy and side effect profile.